ECOLOGICAL ANALYSIS OF THE PHYTOCHEMICALS IN STEM BARKS AND ROOTS OF Calotropis procera (R. BR.), AITON W. T. IN SOME STATES OF NIGERIA. - Lakwannum, G. Y; Olorunmaiye, K. S.; D. Buah, Joshua; K. Ale, Elizabeth; Bako, S. P. (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2017)
Analysis of the Phytochemicals of Calotropis procera in Ilorin and Gombe metropolises has been carried out. 20 freshly matured plants was sampled from each location the stem barks and roots were collected from East and West of the two metropolises, dried under shade and pulverised to powder using mortar and pestle, it was extracted using water, methanol and ethanol. The crude extracts was screened for Phytochemicals. Results revealed presences of alkaloids, flavonoids, saponins, tannin steroids, terpenoids, and glycosides in both selected parts with variations. Simple descriptive statistics was employed and further subjected to analysis of variance (ANOVA) to reveal the variability of the extractants or solvents used both within and between the metropolises. The results shows significant difference in all the extractants for stem barks and roots at (α = 0.05) with p-values as 0.003, 0.020, 0.00 and 0.053, 0.005 and 0.000. for water, methanol and ethanol extracts respectively. A paired t-test was used to compare the Phytochemicals between the metropolises, and there was a significant difference at (α = 0.05). For roots (0.277), and no Significant difference was observed in stem bark (0.002). The ethno botanical information collected revealed that Calotropis procera are commonly used as medicine, firewood, food and as fodder. The variability observed in the occurrence of the Phytochemicals might be attributed to the ability of the solvent to dissolve, differences in the age of the plant, and soil types in the study area.